Pregunta
Evaluate the function at the given values of the independent variable and simplify. \( f(x)=\frac{5 x^{2}-1}{x^{2}} \) \( \begin{array}{lll}\text { (a) } f(5) & \text { (b) } f(-5) & \text { (c) } f(-x)\end{array} \)
Ask by Chambers Cummings. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( f(5) = \frac{124}{25} \), \( f(-5) = \frac{124}{25} \), and \( f(-x) = \frac{5x^{2}-1}{x^{2}} \).
Solución
Substitute \( x=5 \) into the expression \( \frac{5x^{2}-1}{x^{2}} \).
Evaluate the expression by following steps:
- step0: Evaluate:
\(\frac{5x^{2}-1}{x^{2}}\)
- step1: Substitute:
\(\frac{5\times 5^{2}-1}{5^{2}}\)
- step2: Calculate:
\(\frac{5^{3}-1}{5^{2}}\)
- step3: Subtract the numbers:
\(\frac{124}{5^{2}}\)
- step4: Simplify:
\(\frac{124}{25}\)
Substitute \( x=-5 \) into the expression \( \frac{5x^{2}-1}{x^{2}} \).
Evaluate the expression by following steps:
- step0: Evaluate:
\(\frac{5x^{2}-1}{x^{2}}\)
- step1: Substitute:
\(\frac{5\left(-5\right)^{2}-1}{\left(-5\right)^{2}}\)
- step2: Multiply the terms:
\(\frac{5^{3}-1}{\left(-5\right)^{2}}\)
- step3: Subtract the numbers:
\(\frac{124}{\left(-5\right)^{2}}\)
- step4: Simplify the expression:
\(\frac{124}{5^{2}}\)
- step5: Simplify:
\(\frac{124}{25}\)
Substitute \( x=-x \) into the expression \( \frac{5x^{2}-1}{x^{2}} \).
Evaluate the expression by following steps:
- step0: Evaluate:
\(\frac{5x^{2}-1}{x^{2}}\)
The function \( f(x) = \frac{5x^{2}-1}{x^{2}} \) evaluated at the given values of the independent variable are:
(a) \( f(5) = \frac{124}{25} \)
(b) \( f(-5) = \frac{124}{25} \)
(c) \( f(-x) = \frac{5x^{2}-1}{x^{2}} \)
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
The Deep Dive
To evaluate the function \( f(x) = \frac{5x^{2}-1}{x^{2}} \) at the given values: (a) \( f(5) = \frac{5(5^{2}) - 1}{5^{2}} = \frac{5(25) - 1}{25} = \frac{125 - 1}{25} = \frac{124}{25} \) (b) \( f(-5) = \frac{5((-5)^{2}) - 1}{(-5)^{2}} = \frac{5(25) - 1}{25} = \frac{125 - 1}{25} = \frac{124}{25} \) (c) \( f(-x) = \frac{5(-x)^{2} - 1}{(-x)^{2}} = \frac{5(x^{2}) - 1}{x^{2}} = \frac{5x^{2} - 1}{x^{2}} = f(x) \) So: (a) \( f(5) = \frac{124}{25} \) (b) \( f(-5) = \frac{124}{25} \) (c) \( f(-x) = f(x) \)
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium